Ball Milling’s Effect on Pine Milled Wood Lignin’s Structure and Molar Mass - Grigory Zinovyev; Ivan Sumerskii; Thomas Rosenau; Mikhail Balakshin; Antje Potthast (Molecules, 2018)
The effect of ball milling expressed as the yield of milled wood lignin (MWL) on the structure and molar mass of crude milled wood lignin (MWLc) preparation is studied to better understand the process’ fundamentals and find optimal conditions for MWL isolation (i.e., to obtain the most representative sample with minimal degradation). Softwood (loblolly pine) MWLc preparations with yields of 20–75% have been isolated and characterized based on their molar mass distribution (by Size Exclusion Chromatography (SEC)), hydroxyl groups of different types (31P NMR), methoxyl groups (HS-ID GC-MS), and sugar composition (based on methanolysis). Classical MWL purification is not used to access the whole extracted lignin. The results indicate that lignin degradation during ball milling occurs predominantly in the high molar mass fraction and is less pronounced in the low molar mass fraction. This results in a significant decrease in the Mz and Mw of the extracted MWLc with an increase in the yield of MWLc, but has only a very subtle effect on the lignin structure if the yield of MWLc is kept below about 55%. Therefore, no tedious optimization of process variables is necessary to achieve the required MWLc yield in this range for structural studies of softwood MWL. The sugar composition shows higher amounts of pectin components in MWLs of low yields and higher amounts of glucan and mannan in high-yield MWLs, confirming that lignin extraction starts from the middle lamella in the earlier stages of MWL isolation, followed by lignin extraction from the secondary wall region.